2014
DOI: 10.3803/enm.2014.29.2.146
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Multiple Endocrine Neoplasia Type 1 (MEN1) Leads to Misdiagnosis of an Extremely Rare Presentation of Intrasellar Cavernous Hemangioma as MEN1

Abstract: BackgroundMultiple endocrine neoplasia type 1 (MEN1) is a rare inherited disorder characterized by the simultaneous occurrence of endocrine tumors in target tissues (mainly the pituitary, endocrine pancreas, and parathyroid glands). MEN1 is caused by mutations in the MEN1 gene, which functions as a tumor suppressor and consists of one untranslated exon and nine exons encoding the menin protein. This condition is usually suspected when we encounter patients diagnosed with tumors in multiple endocrine organs, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Given the condition that long-term radiographic imaging was helpful for assessing the efficacy of radiation therapy for PICHs, the patient was advised to attend regular follow-up assessments. In addition, it is well known that tumors result from the abnormal expression of genes events, and some recent studies have reported that mutation of some genes was related to development of hemangiomas [21, 22]. If we could perform gene detection in cases of hemangioma of the skull, and then recommend targeted therapy, it could be a prominent topic in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Given the condition that long-term radiographic imaging was helpful for assessing the efficacy of radiation therapy for PICHs, the patient was advised to attend regular follow-up assessments. In addition, it is well known that tumors result from the abnormal expression of genes events, and some recent studies have reported that mutation of some genes was related to development of hemangiomas [21, 22]. If we could perform gene detection in cases of hemangioma of the skull, and then recommend targeted therapy, it could be a prominent topic in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our literature review identified 8 cases of intrasellar cavernous hemangioma (Table 1) [1][2][3][4][5] . All of them were confirmed by pathology, and the mass was completely located in the sella turcica in only 2 of 8 cases, while others extended into the suprasellar cistern and cavernous sinus and encompassed the internal carotid.…”
Section: Discussionmentioning
confidence: 99%
“…Age On MRI, cavernous hemangioma has the following characteristics: well-defined borders, brightly hyperintense on T2WI images, and two pattern enhancement with a rapid homogeneous enhancement and a progressive enhancement. The contrast agent fills the peripheral part of the lesion in the early stage of dynamic contrast-enhanced scanning and then slowly fills the entire lesion [2] . In addition, most pituitary adenomas are hypointense to iso-intense to the normal gland and cerebral cortex on T1-weighted MRI scans and of variable intensity on T2-weighted sequences.…”
Section: Yearmentioning
confidence: 99%
“…The contrast agent fills the peripheral part of the lesion in the early stage of dynamic contrast-enhanced scanning and then slowly fills the entire lesion [2] . In addition, most pituitary adenomas are hypointense to iso-intense to the normal gland and cerebral cortex on T1-weighted MRI scans and of variable intensity on T2-weighted sequences.…”
Section: Yearmentioning
confidence: 99%